ΕΝ ΑΡΧΗΙ ΗΝ Ο ΛΟΓΟΣ: THE LONG JOURNEY OF GRAMMATICAL ANALOGY. (28th February 2019) - Schironi, Francesca
Abstract : Grammar as a discipline devoted to the study of language was greatly advanced by the Alexandrian philologists, and especially by Aristarchus, as demonstrated by Stephanos Matthaios. In order to edit Homer and other literary authors, whose texts were often written in archaic Greek and presented many linguistic problems, the Alexandrians had to recognize linguistic grammatical categories and declensional patterns. In particular, to determine the correct orthography or accentuation of debated morphological forms they often employed analogy, which is generally defined as the doctrine that grammatical forms must follow strict rules of declension. Modern scholars have often opposed the Alexandrian doctrine of analogy to the Pergamene doctrine of 'anomaly', which favoured spoken usage to determine debated forms. Detlev Fehling and David Blank, however, have shown that this strong opposition never really existed and it is mostly due to Varro. More correctly, ancient grammarians identified inflectional rules as well as forms derived from spoken usage or otherwise aberrant forms—however, respect for spoken usage in the latter case was not labelled 'anomaly', which was never a technical term of ancient grammar. Rather, and especially in the Roman period, grammarians used the term 'pathology' to account for and explain irregular forms.